Extensive intestinal necrosis associated with volvulus. Deferred treatment - Mejía Camacho David; Alvarado García Rafael; Jiménez Urueta Pedro S. (Instituto Nacional de Pediatría, 2014)
Intestinal malrotation with volvulus and extensive necrosisis is the deadliest emergency faced by the pediatric surgeon. Treatment consists in surgical repair using the technique described by William Ladd in 1936. In some cases where viability is in questionable a sec- ond look laparotomy upon placement of drains has been described. We report the case of a one month old infant with cloacal extrophy who had an intestinal volvulus. During the surgical procedure necro- sis of more than 90% of the vowel was seen. Surgical drains were placed and second look laparotomy six weeks later was performed with intestinal recovery of 70%.